PERLUASAN CAKUPAN PASAR UMKM MELALUI DIGITAL MARKETING - Ary Armianto; Vita Aprilina; Hadi Mahmudah; Annafi Indratama (Universitas Islam 45 Bekasi, 2022)
In the midst of the COVID-19 pandemic, many new SMEs have sprung up. In order to help MSME compete, MSME need to know about importance of using digital marketing so MSME could get better sales activities. Also providing assistance for MSME to learn how creating business account in digital marketing, in this case writer use instagram business. The program that has been carried out is outreach to MSMEs, providing material on what digital marketing is and providing material on types of digital marketing applications and practicing business Instagram account creation via Zoom. the activity was held on March 9, 2022 on Jl. Graha Harapan Rw 14, Mustika Jaya Subdistrict, Mustika Jaya Village, Bekasi City. the method used is to provide material about what digital marketing is and the types of digital marketing through whatsapp groups, as well as to practice creating business instagram accounts via zoom. The impact of this activity is that people can understand what digital marketing is and the benefits that can be obtained and people has the will to start using digital marketing.